Is near-time prevention for sudden cardiac arrest feasible? The e-MUST score - Karam, Nicole; Bataille, Sophie; Marijon, Eloi; Tafflet, Muriel; Lapostolle, Frederic; Spaulding, Christian; Jouven, Xavier; Lambert, Yves; study investigators, for the e-MUST (Journal of Thoracic Disease; Vol 9, No 6 (June 29, 2017): Journal of Thoracic Disease, 2017)
As underlined by Dr. Montero et al., in-hospital mortality of ST-segment elevation myocardial infarction (STEMI) has decreased drastically, and out-of-hospital death by sudden cardiac arrest (SCA) has become the main cause of death from STEMI (1). SCA is also a major issue of public health with more than 350,000 deaths per year in the United States, accounting for almost half of cardiovascular mortality (2,3). Two approaches have been traditionally used to reduce the burden of SCA: prevention and resuscitation. However, despite major investments in these two approaches, SCA mortality remains high, highlighting the need for new strategies to effectively reduce SCA burden (4). A promising approach would be near-term prevention, which is based on the anticipation of SCA in order to insure that resuscitation will be started soon enough after SCA occurrence, or that prophylactic therapy will be administered for avoiding actual SCA in this well-selected population.